'Protalus ramparts' on Navajo Mountain, Utah, USA:Reinterpretation as blockslope-sourced rock glaciers - Gordon, L S; Ballantyne, C K (Permafrost and Periglacial Processes, 2006)
Transverse ridges crossing broad lobes of coarse debris on a structural bench at similar to 2600-2750 m on Navajo Mountain were interpreted by Blagborough and Breed (1967) as relict protalus ramparts formed by debris cascading down hard snow or firn and accumulating at its downslope margins. Reinvestigation of this site suggests that this interpretation requires revision: there is no rockfall source for the debris, the implied firn gradient is insufficient for supranival debris movement, and the debris lobe microtopography, distal slope gradients and lack of consistent clast-size organization are inconsistent with the characteristics of active protalus ramparts. Alternative origins as moraines, avalanche impact landforms, rockslide runout ridges or the products of snow push or blockslope creep appear implausible. We suggest that the most likely genesis of the debris lobes, their associated ridges and other surface topography is that of rock-glacier creep, through development of massive ice under a cover of coarse debris supplied by movement of blockfield debris down the similar to 24 degrees slope at the rear of the bench. If valid, this interpretation: (1) indicates former permafrost at the time of rampart formation; and (2) implies that classification of rock glaciers requires to be widened to include blockslope-sourced examples. Copyright (c) 2006 John Wiley & Sons, Ltd.